PENGARUH KONTROL DIRI DAN LITERASI KEUANGAN TERHADAP PERILAKU MENABUNG DI BANK KONVENSIONAL - Serli Oktapiani; Sri Andriani; Fifi Apriani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to test the whether of self control has an effect on saving behavior on students to the Faculty of Economics and Business of the University Of Technology Sumbawa. And whether financial literacy has an effect on saving behavior in students of the Economics and Bisiness Faculty of the University Of Technology Sumbawa. This research is a quantitative research. The population of this study were students of the Faculty of Economics and Business University Of Technology Sumbawa. The sample of this study was 100 respondents who were obtained by probability sampling method with stratified random sampling technique. Data collection method using a questionnaire . In proving and analyzing this, multiple linear regression was used. The results of study show tgat : 1) Self-control affects the saving behavior of students from the Economics and Business Faculty of the University Of Technology Sumbawa. 2) Financial literacy affects the saving behavior of students from the Economics and Business Faculty of the University Of Technology Sumbawa. It can be concluded that Self-control and Financial Literacy have a positive and significant effect on saving behavior in conventional banks (students of the Faculty of Economics and Business University Of Technology Sumbawa)